2017
DOI: 10.1038/s41598-017-01601-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced mechanical, thermal, and electric properties of graphene aerogels via supercritical ethanol drying and high-temperature thermal reduction

Abstract: Graphene aerogels with high surface areas, ultra-low densities and thermal conductivities have been prepared to exploit their wide applications from pollution adsorption to energy storage, supercapacitor, and thermal insulation. However, the low mechanical properties, poor thermal stability and electric conductivity restrict these aerogels’ applications. In this paper, we prepared mechanically strong graphene aerogels with large BET surface areas, low thermal conductivities, high thermal stability and electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(90 citation statements)
references
References 47 publications
3
86
0
1
Order By: Relevance
“…The average pore sizes of MGO‐NH 2 , MGO‐PAMAM‐G1.0, HMGO‐NH 2 , and HMGO‐PAMAM‐G1.0 are 6.8536, 5.9751, 15.5569, and 15.4874 nm, respectively, indicating the existence of mesoporous. Moreover, based on the BET model, the BET surface area of HMGO‐NH 2 (48.7298 m 2 ·g −1 ) and HMGO‐PAMAM‐G1.0 (44.4232 m 2 ·g −1 ) are much less than MGO‐NH 2 (112.7007 m 2 ·g −1 ) and MGO‐PAMAM‐G1.0 (126.3983 m 2 ·g −1 ) due to the formation of longer hydrophobic chain resulted in its average pore size increased . The above comparative analysis could provide a basis for subsequently exploring the adsorption mechanism of samples.…”
Section: Resultsmentioning
confidence: 91%
“…The average pore sizes of MGO‐NH 2 , MGO‐PAMAM‐G1.0, HMGO‐NH 2 , and HMGO‐PAMAM‐G1.0 are 6.8536, 5.9751, 15.5569, and 15.4874 nm, respectively, indicating the existence of mesoporous. Moreover, based on the BET model, the BET surface area of HMGO‐NH 2 (48.7298 m 2 ·g −1 ) and HMGO‐PAMAM‐G1.0 (44.4232 m 2 ·g −1 ) are much less than MGO‐NH 2 (112.7007 m 2 ·g −1 ) and MGO‐PAMAM‐G1.0 (126.3983 m 2 ·g −1 ) due to the formation of longer hydrophobic chain resulted in its average pore size increased . The above comparative analysis could provide a basis for subsequently exploring the adsorption mechanism of samples.…”
Section: Resultsmentioning
confidence: 91%
“…The graphene aerogel can recover completely after more than 90% compression [5]. Recently, Cheng et al reported that 75.0 mg graphene aerogel cylinder could support a 2kg counterpoise, at least 26000 times their own weight as can be seen in the figure 6 [11]. Figure 6.…”
Section: Specific Properties Of Cnt and Grapheneaerogelsmentioning
confidence: 99%
“…Figure 6. CNT &Graphene Aerogels are extremely elastic, bouncing back after being compressed [5,11]. f).…”
Section: Specific Properties Of Cnt and Grapheneaerogelsmentioning
confidence: 99%
“…This combination microstructure was designed to provide an even greater opportunity to enhance λ due to a significantly higher intrinsic λ (about 3000 W/mK) of GNS and MWCNT [23][24][25][26][27][28][29][30] than that of other high-thermal conductivity ceramic fillers, such as aluminium nitride (AlN) and boron nitride (BN). Moreover, AgNPs were chosen because of their high thermal conductivity of Ag (λ = 429 W/(mK)) [6,24]. AgNPs functionalized GNS and MWCNT showed a higher σ in functionalized fillers, forming a more effective thermally conductive network and hence, lowering the ITR effect.…”
Section: Introductionmentioning
confidence: 99%